“A gente nasceu nessa terra, é onde está nossa raiz”. ensino de história em vista da luta camponesa em Itaitinga, Ceará (1980-1990) - Machado, Antonio Regiano de Lima (2025)
Brazil remains one of the most unequal countries in the world in terms of access to arable land, within a context marked by rural violence and land concentration in the hands of large proprietors. Thus, the Agrarian Issue is one of the central themes for reflecting on Brazil, and here we highlight the relevance of studying peasant struggles starting in elementary school. This work presents a proposal for the teaching of History, concerning peasant struggles, with students from Escola Municipal Demócrito Rocha, considering the peasant resistance movements in Itaitinga, Ceará, during the 1980s and 1990s. The proposal is based on the understanding that the struggle for land is part of the peasants' history, whether in rural or urban areas. The study begins with historiographical research on peasants, with an emphasis on land struggles, as well as research on the teaching of History, highlighting education as an emancipatory practice. A central point of the Dissertation is the investigation of the agrarian issue in Itaitinga, Ceará, which began prior to its political emancipation, when there was significant mobilization of peasants and their families, starting with the construction of the Riachão dam, inaugurated in 1981 through the damming of the Pacoti river. The output of the research led to the development of a Teaching Plan designed for Basic Education, structured in seven sessions and incorporating a variety of historical sources, which played a central role in the didactic-pedagogical strategies. The experiencing at Escola Demócrito Rocha led to the creation of multiple materials by the students, such as School Newspapers and Learning Journals. Oral History also stands out as an important aspect of the investigation; making it possible to include new subjects—both men and women—in the development of the peasant movement in Itaitinga, Ceará, as evidenced by interviews and other sources. Thereby, the thread of peasant memory becomes an unavoidable path, explored here in terms of the agency of individuals and their acts of resistance. In the propositional part of the study, we adopted a methodology that encourages the problematization of contents in History classes, related with the students' realities, as well as a deepening on the reflection of the role of the teacher, researcher, author, and agent of transformational History teaching. In conclusion, we highlight the proposed Teaching Plan and the materials created by the students (the thirty-six Learning Journals and ten School Newspapers) as key outcomes of this research.